PEMBERIAN MAKANAN TAMBAHAN (PMT) DENGAN KENAIKAN BERAT BADAN IBU HAMIL KEK - Fitri Juliasari; Elsa Fitria Ana (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2021)
Nutritional problems are one of the indirect causes of maternal and child mortality which can be prevented. The condition of pregnant women with CED is at risk of decreasing muscle strength that helps the delivery process, that it can result in fetal death (miscarriage), premature birth, birth defects, low birth weight babies and even infant death. The design used is quantitative with a cross-sectional approach with univariate and bivariate analysis by using the Chi-Square test. The population were all pregnant women who did pregnancy check at Putih Doh Public Health Center in 2020. The samples used the Random Sampling technique. This research was conducted April 2021 at Putih Doh Public Health Center using secondary data from history of pregnant women examination during 2020. The results showed that were given supplementary feeding 17.9% and not given it 82.1%. The respondents who experienced weight gain were 98.5% and did not experience weight gain were 1.5%. The results of statistical test are p-value <0.005, which means there is relationship between Supplementary Feeding with weight gain of pregnant women with CED at Putih Doh Public Health Center area 2020. It is expected that health workers will carry out special monitoring of pregnant women with CED in consuming supplementary feeding and balanced nutritional foods